Conservation farming in Zambia - Haggblade, Steven; Tembo, Gelson (International Food Policy Research Institute, 2003)
Since 1996, a growing coalition of stakeholders from the private sector, government and donor communities has promoted a new package of agronomic practices for smallholders in Zambia. The conservation farming (CF) system they advocate involves: dry-season land preparation using minimum tillage methods (either ox-drawn rip lines or hand-hoe basins laid out in a precise grid of 15,850 basins per hectare); no burning but rather retention of crop residue from the prior harvest; planting and input application in fixed planting stations; and nitrogen-fixing crop rotations. The CF system enables farmers to plant with the first rains when seeds will benefit from the initial nitrogen flush in the soil. By breaking pre-existing plow-pan barriers, the CF basins and rip lines improve water infiltration, water retention and plant root development. The precise layout of grids and planting lines enables farmers to locate fertilizer and organic material in close proximity to the plants, where they will provide greatest benefits. Evidence from similar technologies in other parts of Africa suggests that the effectiveness of conservation farming will vary not only across regions but also across crops and over time, due to variations in weather and rainfall. In addition, many of the benefits of CF -- including improved soil structure, gains from nitrogen-fixing crop rotations and reduced field preparation labor -- occur gradually and over time. Therefore, it will be important to establish long-term monitoring efforts for conservation farming and control plots across a broad range of geographic settings, crops and seasons. Results and their interpretation are from a survey of 125 farms in Central and Southern provinces during the 2001/2 cropping season.